Critical Glenoid Bone Loss in Posterior Shoulder Instability. Issue 5 (April 2018) - Nacca, Christopher; Gil, Joseph A.; Badida, Rohit; Crisco, Joseph J.; Owens, Brett D.
Background: There is currently no consensus regarding the amount of posterior glenoid bone loss that is considered critical. Critical bone loss is defined as the amount of bone loss that occurs in which an isolated labral repair will not sufficiently restore stability. Purpose: The purpose is to identify the critical size of the posterior defect. Study Design: Controlled laboratory study. Methods: Eleven cadaveric shoulders were tested. With the use of a custom robot device, a 50-N compressive force was applied to the glenohumeral joint, and the peak force that was required to translate the humeral head posteriorly and the lateral displacement that occurred with translation were measured. The defect size was measured as a percentage of the glenoid width. Testing was performed in 11 conditions: (1) intact glenoid and labrum, (2) simulated reverse Bankart lesion, (3) the reverse Bankart lesion repaired, (4) a 10% defect, (5) the reverse Bankart lesion repaired, (6) a 20% defect, (7) the reverse Bankart lesion repaired, (8) a 30% defect, (9) the reverse Bankart lesion repaired, (10) a 40% defect, and (11) the reverse Bankart repaired. Results: Force and displacement decreased as the size of the osseous defect increased. The mean peak force that occurred with posterior displacement in specimens with a glenoid defect ≥20% and a reverse Bankart repair (13 ± 9 N) was significantly lower than the peak force that occurred in specimens with an isolated reverse Bankart repair (22 ± 10 N) ( P = .0451). In addition, the mean lateral displacement was significantly less in the specimens with a 20% glenoid defect and a reverse Bankart repair (0.61 ± 0.57 mm) compared with the lateral displacement that occurred in specimens with an isolated reverse Bankart repair (1.6 ± 0.78 mm) ( P = .0058). Conclusion: An osseous defect that is ≥20% of the posterior glenoid width remains unstable after isolated reverse Bankart repair. Clinical Relevance: A bony restoration procedure of the glenoid may be necessary in shoulders with a posterior glenoid defect that is ≥20% of the glenoid width.